Gender Equality Indicators in Ukraine: Impact Analysis of Gender Initiatives - Akbash, K.; Pasichnyk, N.; Rizhniak, R. (Statistics of Ukraine, 2025)
The article presents the results of a study on determining the impact of gender initiatives on indicators of gender equality in Ukraine. For analysis, the authors chose the Gender Development Index and the Gender Inequality Index, as well as their composite indicators. The gradation of gender initiatives was carried out using the following scale: general issues of gender equality; development of gender-sensitive legislation; conducting a gender audit; introducing a gender component into educational programs; combating gender stereotypes and discrimination; protection from gender-based violence; gender-responsive budgeting. The result of the study was the following practical conclusions. Firstly, the correlation analysis between gender indices (Gender Development Index and Gender Inequality Index) and the total number of gender initiatives showed that gender initiatives have a significant impact on key indicators of gender development and gender inequality in Ukraine. Secondly, the forecast of stable values ​​for the Gender Development Index indicates that we should not expect significant changes in this index in the coming years. This may indicate the sustainability of gender policies and the level of equality, but at the same time it indicates that global changes may not be fast enough. Third, the decline in the Gender Inequality Index indicates potential positive changes. The forecast for the coming years shows the possibility of reducing inequality, which could be the result of successful reforms and policies. Fourthly, the forecast of a decrease in the number of gender initiatives is a signal for a review of the current situation in the field of gender equality. A significant decline in activity may indicate that greater efforts should be made to support and implement new programs to combat gender inequality. However, these forecasts only partially take into account possible changes caused by military events in Ukraine. The factor of war can significantly affect these indicators, leading to increased inequality or even decreased access to basic rights and resources for women and minorities. The impact of war on the number of gender initiatives may be even more pronounced because in times of war, states may cut funding for social programs or focus on rebuilding infrastructure rather than promoting gender equality. This could lead to a sharp reduction in the number of initiatives or their cancellation. Taking this factor into account is important for adjusting policy strategies and initiatives that aim to support equality in the face of global upheaval.